2020
DOI: 10.3389/fpsyg.2020.01635
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the “Erasing Race” Effect in the United States and Some Theoretical Considerations

Abstract: The "erasing race" effect is the reduction of the salience of "race" as an alliance cue when recalling coalition membership, once more accurate information about coalition structure is presented. We conducted a random-effects model meta-analysis of this effect using five United States studies (containing nine independent effect sizes). The effect was found (ρ = 0.137, K = 9, 95% CI = 0.085 to 0.188). However, no decline effect or moderation effects were found (a "decline effect" in this context would be a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This means that cognitively impairing forms of discrimination are likely associated with the purely socially constructed aspects of SIRE (those that are wholly independent of heritable ancestry-related phenotypes such as skin reflectance or color). It has been found that 'race' as a concept may, to a substantial degree, be a byproduct of social coalitional categorization, the significance of which can be 'erased' once alternative social cues are presented that more accurately map onto relevant coalitional structure (Kurzban et al, 2001; for a meta-analysis of 'erasing race' effects, see Woodley of Menie et al, 2020); thus, there is likely much about 'race' and related phenomena that exists purely in the psychological (and also sociological) realm and that is wholly divorced from outward markers of biogeographic ancestry. Elucidating the processes that go into the construction and persistence of such 'social forces' goes well beyond the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This means that cognitively impairing forms of discrimination are likely associated with the purely socially constructed aspects of SIRE (those that are wholly independent of heritable ancestry-related phenotypes such as skin reflectance or color). It has been found that 'race' as a concept may, to a substantial degree, be a byproduct of social coalitional categorization, the significance of which can be 'erased' once alternative social cues are presented that more accurately map onto relevant coalitional structure (Kurzban et al, 2001; for a meta-analysis of 'erasing race' effects, see Woodley of Menie et al, 2020); thus, there is likely much about 'race' and related phenomena that exists purely in the psychological (and also sociological) realm and that is wholly divorced from outward markers of biogeographic ancestry. Elucidating the processes that go into the construction and persistence of such 'social forces' goes well beyond the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies were identified by searching APA PsycInfo, PubPSYCH, PSYNDEX, and Google Scholar with the following search terms: (categori* OR group* OR stereotyp*) AND (race OR ethnic* OR [black AND white]) AND (“memory confusion” OR “statement confusion” OR “who said what” OR “who-said-what” OR “error difference” OR “within category”). Additionally, the reference lists of two published “Who said what?” meta-analyses (Pietraszewski, 2018; Woodley Of Menie et al, 2020) were searched manually for relevant literature. Email requests were sent to the Society for Personality and Social Psychology, European Association of Social Psychology, and German Psychological Society mailing lists, and the labs of Juliane Degner in Hamburg and K. C. Klauer in Freiburg were contacted personally.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the reference lists of two published "Who said what?" meta-analyses (Pietraszewski, 2018;Woodley Of Menie et al, 2020) were searched manually for relevant literature. Email requests were sent to the Society for Personality and Social Psychology, European Association of Social Psychology, and German Psychological Society mailing lists, and the labs of Juliane Degner in Hamburg and K. C. Klauer in Freiburg were contacted personally.…”
Section: Literature Searchmentioning
confidence: 99%
“…Additionally, the reference lists of two published "Who said what?" metaanalyses (Pietraszewski, 2018;Woodley Of Menie et al, 2020) were searched manually for relevant literature. Email requests were sent to the Society for Personality and Social Psychology (SPSP), European Association of Social Psychology (EASP), and German Psychological Society (DGPs) mailing lists, and the labs of Juliane Degner in Hamburg and K. C. Klauer in Freiburg were contacted personally.…”
Section: Literature Searchmentioning
confidence: 99%